P411 Acceptability of a phone app-based motivational interviewing intervention for young men's sexual health. (14th July 2019) - Guzman, Alexis; Landers, Sara; Nechitilo, Meredith; Catallozzi, Marina; Gold, Melanie; Bell, David; Rosenthal, Susan
Abstract : Background: Motivational interviewing (MI) is an effective communication style for facilitating behavior change. Pairing MI with a smartphone app has the potential to engage young men, a traditionally hard-to-reach population. We assessed young men's experiences in a pilot study examining the use of a smartphone app with phone-based MI coaching by trained community health coaches (one female, one male). Methods: Fourteen (of 26) predominantly black and Hispanic men, ages 16–19 years, who participated in the pilot study were interviewed about their experience. They participated in app activities and coaching that addressed sexual health or fitness (comparison group). Interviews were transcribed and coded using thematic analysis. Results: Participants found the app activities and coaching to be acceptable. In both arms, the young men were asked about sexual health and reported being comfortable discussing it in this format. In the sexual health arm, they reported gaining knowledge about contraceptive methods and sexually transmitted infections, which some shared with their sexual partners. Participants were comfortable with the coach's gender; a benefit of a female coach was her perspective on sexual health. Most preferred phone rather than in-person or video coaching sessions due to not having to travel, ease of rescheduling sessions, and increased privacy regarding sensitive subjects. The most common obstacle to participation was phone replacement; others included parental monitoring and restriction of phone privileges. Over time, the young men felt positively about their connection to the coach. They sometimes viewed the coach as having medical expertise beyond the scope of his/her training. Conclusion: Phone app-based MI with community health coaches has great potential for use with young men for a variety of health issues including sexual health; however, it has unique obstacles. Phone accessibility may restrict young men's ability to fully engage and perceptions of a coach's expertise should be regularly clarified. Disclosure: No significant relationships.